Is Rickettsia amblyommii able to regulate long non-coding RNA expression in Amblyomma sculptum tick? An in silico approach - Barcelos, Rafael Mazioli (2017)
The Amblyomma sculptum tick belongs to Amblyomma cajennnense complex, the most important taxon in transmission and host for Rickettsia rickettsii bacteria, the main etiologic agent of Brazilian Spotted Fever in Brazil and Rocky Mountain Spotted Fever in USA. As a member of this species complex, A. sculptum tick is actually very important under human and veterinary subject acting as vector for this zoonotic agent in Brazil. Its role in biological cycle of rickettsia strains, as well Rickettsia-tick interactions, still need to be better understood since recent studies found these strains infecting A. sculptum ticks. As putative modulators of these pathogen-host interaction, the roles of long non-coding RNAs (lncRNA) of ticks are unknown and need to be discovered and characterized. The lncRNAs are involving in modulation of a plethora of cell activities as transcription, gene silencing and chromosome opening, for example. Thus, herein we present an in silico approach for analyze the modulation of lncRNAs by R. amblyommii in A. sculptum tick. Using previously published data sets of A. sculptum transcriptomes, we identified putative lncRNAs and evaluated for differential expression in midgut and ovaries in this tick specie. Two assemblers were tested, Trinity and CLC Genomics, to construct the contigs and a pipeline to select the sequences with lncRNA characteristics. We obtained 31,888 and 23,733 contigs of putative lncRNAs using Trinity and CLC Genomics, respectively. We further identified more than 500 sequences of putative lncRNA that significantly aligned to sequences of RefSeq RNA, RNA Central and NONCODE databases. The transcriptome analysis further suggests that R. amblyommii is inducing differential expression of putative lncRNAs in midgut and ovary tissues. The work herein contributes for tick lncRNA database increasing and the initials insights of which lncRNA sequences are involving in Rickettsia-tick relationship